Optimization of cabinet drying conditions for dried moringa leaves by Response Surface Methodology - Md. Abdul Alim; Monirul Islam; Shirina Akter; Safa Maroua; Ashraful Alam; Md. Esrafil; Md. Azizul Haque; Rokeya Begum (Journal of Agriculture and Food Research, 2023)
The present study has been carried out to optimize the cabinet drying conditions using Response Surface Methodology (RSM) for drying moringa leaves. Moringa leaves were dried by a cabinet dryer using different drying temperatures 40–70 °C and air velocity 1.3–1.65 m/s. A central composite design was applied to optimize the drying conditions. The combined effect of these variables on the responses (moisture content, L*, a*/b* value, and vitamin C) was investigated. The findings show that the generated regression models effectively captured the real link between the independent variables and the outcomes as well as sufficiently described the variation in the data. The moisture content, L* value, a*/b* value, and vitamin C content of dried moringa leaves were 3.76–8.30%, 42.17-45.39, −0.498 to −0.581, 10.50–19.57 mg/100g, respectively. The study found that the maximum vitamin C content was 19.57 mg/100g at 33.7 °C and 1.45 m/s air velocity. On the other hand, minimum moisture content was found 3.76% at 76.2 °C and 1.45 m/s air velocity. The optimum conditions for maximization of vitamin C and minimization of moisture content were the drying temperature and air velocity of 40 °C and 1.45 m/s, respectively. Moisture content, L*, a*/b*, and vitamin C content at optimum conditions were 6.282%, 44.282, −0.536, 17.711 mg/100g, respectively. Therefore, the current study suggests that the derived model is suitable for the enhanced retention of color ratio, lightness, and vitamin C content with a longer shelf life, which can afterward be practical in large-scale production in the food industry.